Comparison of chimeric mouse-human and humanized anti-CD25 monoclonal antibodies for steroid-refractory acute graft-versus-host disease - Zheng, Xinhui; Zhou, Yunxia; Zheng, Yawei; Lu, Ni; Cao, Yigeng; Zhai, Weihua; Wei, Jialin; Yang, Donglin; Zhang, Rongli; Pang, Aiming; Feng, Sizhou; Han, Mingzhe; et al. (Frontiers in Immunology, 2026)
IntroductionSteroid-refractory acute graft-versus-host disease (SR-aGVHD) represents a severe and persistent complication that can arise following allogeneichematopoietic stem cell transplantation (allo-HSCT). This study aimed toassess the effectiveness and safety of basiliximab compared with those of a humanized anti-CD25 monoclonal antibody (xenopax) in the treatment of SR-aGVHD in patients who underwent allo-HSCT.MethodsThis retrospective trial included 32 patients diagnosed with SR-aGVHD who were administered xenopax at 1 mg/kg on days 1, 4, and 8, and weekly thereafter until aGVHD severity was reduced to below grade 2. A historical cohort of 37 patients received basiliximab, which is a chimeric mouse-human anti-CD25 antibody.ResultsThe overall response (OR) rate on day 28 was not significantly different between The xenopax and basiliximab groups, with rates of 82% and 72%, respectively (p=0.57). Additionally, no differences were observed between the groups regarding the safety profile. The 1-year overall survival (OS) and non-relapse mortality (NRM) rates in the xenopax and basiliximab cohorts were 64% versus 40% (p=0.06) and 45% versus 48% (p=0.46), respectively.DiscussionIn conclusion, no significant differences were observed in efficacy or adverse events between chimeric mouse-human and humanized anti-CD25 monoclonal antibodies for the treatment of SR-aGVHD. Further studies with larger cohorts are necessary to validate these findings.